DENTAL LASERS IN RESTORATIVE DENTISTRY: A REVIEW - Doriana Agop-Forna; Mihaela Sălceanu; Claudiu Topoliceanu; Cosmin Creţu; Decebal Vasincu; Norina Forna (Romanian Society of Oral Rehabilitation, 2021)
Use of lasers in restorative dentistry fields brings many advantages both for dental practitioner and patients. Dental lasers can assist restorative procedures in treatment of dental caries, endodontic mechanical preparation and root canals decontamination, periodontal pockets decontamination, periodontal regenerative procedures, sulcus uncovering, and crown lenghtening. Features of laser-assisted procedures in restorative treatments of vital and non-vital teeth are as follows: absence or a low level of pain; absence of vibrations; reduction of patient's anxiety; selective removal of infected dentin; decontamination of root cement and periodontal sulcus; elimination of the pulp or periapical area damage risk; faster periodontal tissues regeneration; faster healing of gingival tissues following crown lengthening or sulcus uncovering.